What are the priorities of consumers and carers regarding measurement for evaluation in mental healthcare? Results from a Q-methodology study - Rachel O'Loughlin; Caroline Lambert; Gemma Olsen; Kate Thwaites; Keir Saltmarsh; Julie Anderson; Nancy Devlin; Harriet Hiscock; Kim Dalziel (BMC, 2024)
Abstract Background The purpose of this study was to identify and describe common views of people with lived experience of mental health challenges - consumers and carers, families and supporters - of what they consider the most important measures to include in health economic evaluations which assess the incremental value of competing options in mental health care. Methods Participants (n = 111) were people living in the state of Victoria, Australia, who identified as consumers of mental healthcare (n = 38); carers, family members and/or supporters (n = 43); or both (n = 30). Factor analysis based on Q-Methodology was used to identify clusters of people who hold similar viewpoints. Common viewpoints were described in terms of the characteristics of the group, and a qualitative interpretation was conducted on the basis of distinguishing statements and quotes provided in participants' own words. Results We identified four common views: (1) safety before all else, prioritizing physical, sexual and psychological safety; (2) hope and partnership in processes of care; (3) physical and emotional health and wellbeing; and (4) care access, continuity and partnership with families. Although different priorities were identified for each viewpoint, key priority areas that were common to all views were having an environment in the health service that fosters respect and dignity, and that consumers feel heard and listened to. In sub-group and qualitative analyses, differences were observed regarding the likelihood of consumers and carers holding each of the views, as well as by age group. Conclusions While some differences were noted between the views of consumers and carers and different age groups, there was also common ground regarding what outcomes are of most importance to measure. Including these measures in evaluation frameworks would provide a way of focussing mental healthcare decisions on the aspects of mental healthcare that are of most value to consumers and carers, thereby addressing an important shortcoming of current approaches to decision-making in mental healthcare.